The immunosuppressive tumour network: myeloid‐derived suppressor cells, regulatory T cells and natural killer T cells. Issue 2 (16th January 2013) - Lindau, Dennis; Gielen, Paul; Kroesen, Michiel; Wesseling, Pieter; Adema, Gosse J.
Summary Myeloid‐derived suppressor cells (MDSC) and regulatory T (Treg) cells are major components of the immune suppressive tumour microenvironment (TME). Both cell types expand systematically in preclinical tumour models and promote T‐cell dysfunction that in turn favours tumour progression. Clinical reports show a positive correlation between elevated levels of both suppressors and tumour burden. Recent studies further revealed that MDSCs can modulate the de novo development and induction of Treg cells. The overlapping target cell population of Treg cells and MDSCs is indicative for the importance and flexibility of immune suppression under pathological conditions. It also suggests the existence of common pathways that can be used for clinical interventions aiming to manipulate the TME. Elimination or reprogramming of the immune suppressive TME is one of the major current challenges in immunotherapy of cancer. Interestingly, recent findings suggest that natural killer T (NKT) cells can acquire the ability to convert immunosuppressive MDSCs into immunity‐promoting antigen‐presenting cells. Here we will review the cross‐talk between MDSCs and other immune cells, focusing on Treg cells and NKT cells. We will consider its impact on basic and applied cancer research and discuss how targeting MDSCs may pave the way for future immunocombination therapies.